Edukasi Gizi dan Kesehatan pada Remaja Komunitas Adat Suku Anak Dalam (SAD) Desa Pematang Kabau Kabupaten Sarolangun - Merita Merita; Dini Junita; Dwi Yunita Rahmadhani (Jurnal Abdimas Kesehatan (JAK), 2020)
Adolescent nutrition and health issues need to be considered because adolescents are the next generation that determines the quality of human resources. Likewise, adolescents who are living in marginal conditions such as the Suku Anak Dalam (SAD) need to receive special attention due to the lack of access to information and nutrition education in these groups. Therefore, the purpose of this service is to educate adolescent nutrition and health in the indigenous community of Suku Anak Dalam (SAD). This activity was carried out in June - August 2020, in Pematang Kabau Village, Sarolangun Regency. The target is 10 SAD adolescents. This activity consists of providing education with power point media, leaflets, posters, and videos, as well as demonstrations using food models. The outputs of the community service activities are: (1) Media leaflets and health nutrition posters and; (2) Application of balanced nutrition in adolescents. The results showed that  a better change to aspects of nutritional knowledge where most targets can recognize and mention foods that are good for health, and can exemplify simple ways of monitoring nutritional status such as weighing, height, and measurement of Upper Arm Circumference. Based on this activity it is necessary to collaborate efforts from village officials, nutrition cadres and health workers to carry out routine nutrition and health monitoring on SAD adolescents so as to improve the health status of the SAD community.